Style and self‐making: String bag production in the Papua New Guinea Highlands. Issue 5 (October 2015) - Andersen, Barbara
<x xml:space="preserve">Abstract</x> The looped netbag or bilum is one the most culturally significant of everyday objects in Papua New Guinea (PNG). Made exclusively by women, bilum are also iconic of female productive and reproductive labour. In this article, I analyze how growing social stratification is expressed through the types of bilums young women produce and wear. I argue that the choices that young women make about what kinds of designs, shapes, colours, and fashions to incorporate into their bilums can tell us a great deal about their desires, experiences, and imaginings. While previous analyses have focused on the bilum as an ambiguously gendered object expressing complex ideas about sexual difference, I argue that bilum style increasingly indexes complex ideas about geography and social location, materializing contemporary Papua New Guinean 'imaginaries' of space.